“Olinda, patrimônio que educa”: avaliação da implementação do Programa Educar pra Valer em Olinda/PE - Barbosa, Hannah Guimarães (2022)
Quality education is everyone's right. However, Brazilian public education still faces many challenges, and with the aggravation of the Covid-19 pandemic, it has been indicated that the problems related to the low level of student learning and the significant inequalities should worsen even more in the coming years. When analyzing the performance of its students in large-scale assessments, the city of Olinda, PE, observed that most of them were at deficient levels concerning literacy skills. Therefore, in 2019, it signed a cooperation agreement with Associação Bem Comum (ABC) intending to implement changes in the educational policy of the public school system based on the guidelines and methodology of the Educar pra Valer Program (EpV), which in the municipality was called Olinda Program, Heritage that Educates. The primary objective of the research proposed here is to evaluate the program implementation process in Olinda, PE. The time period refers to the years 2019 to 2022, which corresponds to the duration of the partnership between the EpV and the municipality. The assessment was conducted based on the paradigm of depth assessment combined with process assessment. The research used qualitative methodology and the methodological instruments applied were: bibliographic and documental research; technical visits, semi-structured interviews, and questionnaires; and institutional data collection. The analysis of results was contingent on content analysis and triangulation of methods. The findings indicate that the program's actions had a beneficial impact on the performance of children from Olinda, especially in literacy. The focus is on developing the fluency of students in the early years of elementary school through the delivery of structured teaching materials, training for teachers, trainers, and school administrators, and the establishment of a culture of evaluation and monitoring of learning, among other actions, resulted in improved schooling, despite the obstacles posed by the Covid-19 pandemic.